The Relationship Between Young Adult’s Lifestyle about Hypertension in The Working Area at Bunturaja PHC Dairi - Herlina Evi Yanti Manik; Perak M.A. Hutagalung (Institute of Computer Science (IOCS), 2020)
One disease that is becoming a trend today is hypertension. One billion people are having problems with hypertension that triggers stroke and heart events. This study aims to determine the risk factors for the incidence of hypertension in the Work Area of Bunturaja Public Health Center, Dairi Regency in 2018. This type of research is analytic observational with a case control study design. The population of this study were all patients who visited the Bunturaja Community Health Center in 2018 and recorded in a medical record book. The study sample was patients who had hypertension and did not suffer from hypertension with a ratio of cases and controls 1: 1 consisting of 33 cases and 33 controls. Data analysis was performed with CI = 95% and using odds ratio (OR) test. The results of the Chi Square test in the case group showed that there was a significant relationship between diet and hypertension p = 0.001 and the OR = 0.6548 CI (0.206-2.076). There is a significant relationship between activity and the incidence of hypertension with a value of p = 0.000 and OR = 0.10 CI (95%) = 0.120-2.318. Smoking habits had no significant relationship with p> 0.05 (p = 0.091 and OR 1.834 (CI = 0.667-5.037). There was a significant relationship between drinking alcohol and hypertension with an OR value of 2.356 (CI = 0.413-13.449) p value <0.05, namely (0.02). There was no significant relationship between stress levels and the incidence of hypertension with a p value = 0.210 and an OR of 1.578 (0.569-4.381). It is recommended that Bunturaja Puskesmas further increase the BINDU POS (posyandu for non-communicable diseases at the age of 15-44 years) so that it is easy to detect people with hypertension, especially in young adults The need for blood pressure checks, regular medication, and living a healthy lifestyle.